PEMANFAATAN SILASE DAUN UBIKAYU UNTUK PAKAN TERNAK KAMBING - Eko Marhaeniyanto (BUANA SAINS, 2007)
This experiment that was aimed to evaluate the usage of various additives to prepare cassava leaf silage and to study the response of the goat fed with the silage was conducted at the Livestock Research Station in Prodo, Klampok Singosari Malang. This experiment consisted of two periods. The first period was aimed to evaluate the usage of seven additive treatments used for preparing cassava leaf silage, while the second period was aimed to evaluate the response of the goat fed with the cassava leaf silage. Nine male goats aged 3-6 months with an initial body weight of 15,767 ± 2,516 kg each were allotted to 3 treatments with 3 replications in a randomized block design. The goat was fed with chopped elephant grass and three different levels of cassava leaf silage as treatments. During the experiment, daily amount of feed offered and refused, and their samples were taken for proximate analysis of DM, organic matter (OM) and crude protein (CP) content to measure feed intake. The results showed that the different treatments of cassava leaf silage fed on the goats did not significantly affect DM intake, OM intake, CP intake and average daily weight gain